2007
DOI: 10.1021/jf072423r
|View full text |Cite
|
Sign up to set email alerts
|

α-Chaconine-reduced Metastasis Involves a PI3K/Akt Signaling Pathway with Downregulation of NF-κB in Human Lung Adenocarcinoma A549 cells

Abstract: Alpha-chaconine, isolated from Solanum tuberosum Linn., is a naturally occurring steroidal glycoalkaloid in potato sprouts. Some reports demonstrated that alpha-chaconine had various anticarcinogenic properties. The aim of this study is to investigate the inhibitory effect of alpha-chaconine on lung adenocarcinoma cell metastasis in vitro. We chose the highly metastatic A549 cells, which were treated with various concentrations of alpha-chaconine to clarify the potential of inhibiting A549 cells invasion and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 25 publications
3
44
1
1
Order By: Relevance
“…Existing data indicate that the MAPK pathway is related to paclitaxel-or K8-induced cell death in three different human cancer cell lines: HeLa cervical carcinoma, MCF7 breast cancer, and A431 squamous carcinoma cells (Bacus et al, 2001). The mitogen-induced ERK MAPKs are linked to cell proliferation and survival, whereas the stress-activated MAPKs, p38, and JNK are involved in apoptosis (Wang et al, 2004;Shih et al, 2007). Here, we found that paclitaxel or K8 alone induced ERK activation, whereas the combination of these two compounds synergistically induced activation of ERK (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Existing data indicate that the MAPK pathway is related to paclitaxel-or K8-induced cell death in three different human cancer cell lines: HeLa cervical carcinoma, MCF7 breast cancer, and A431 squamous carcinoma cells (Bacus et al, 2001). The mitogen-induced ERK MAPKs are linked to cell proliferation and survival, whereas the stress-activated MAPKs, p38, and JNK are involved in apoptosis (Wang et al, 2004;Shih et al, 2007). Here, we found that paclitaxel or K8 alone induced ERK activation, whereas the combination of these two compounds synergistically induced activation of ERK (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al [114] reported that tangeretin inhibited platelet-derived growth factor-(PGDF-) BB-induced proliferation and migration of aortic smooth muscle cells by blocking AKT activation in a dose-dependent manner. The existing study indicated that the FAK/PI3K/Akt is involved in the regulation of MMP-2 and MMP-9 activities on different cell types [115]. In addition, NF-κB has been known to translocate to the nucleus and regulate the expressions of multiple genes involved in MMP-2/MMP-9 secretions.…”
Section: Anti-metastasismentioning
confidence: 99%
“…In our previous report, we found that a-chaconine inhibited A549 cell metastasis by a reduction of MMP-2 and MMP-9 activities involving suppression of JNK and the PI3K/Akt/NF-kB signaling pathway. 33) a-Chaconine and a-solanine are major glycoalkaloids in potato and differ only in the nature of the carbohydrate side chain attached to the 3-OH group of solanidine. Thus, we suggested that these two structural similar compounds possess similar antimetastatic potential.…”
Section: )mentioning
confidence: 99%